Stature estimation and its reliability in different types of dental alignment using the Carrea’s Index - Priyadershini Rangari; Udaybhan Singh; Nivedita Singh; Suhas G. Kamdi (International Journal of Medical Research and Review, 2018)
Introduction: Estimation of stature holds a special place in the field of forensic medicine.Objectives: This study was designed to investigate the ability of estimating stature from the dimensions of lower anterior teeth.Method: The study was carried out by taking the measurement from the mesio-distal widths of lower central incisor, lateral incisor and canine of 100 undergraduate students for examination. Each hemiarch was considered separately equaling 200 inferior hemi-arches, which were divided according to the dental alignment into normal, crowded and diastema and the measurements (arch and chord) were made with a ‘divider caliper’.Result: A statistically significant difference between the types of dental arch was obtained for both males and females with regards to the different dental alignments; higher correlation between stature the arch for normal alignment (r=0.9658; r =0.8347); moderate correlation for crowded alignment (r=0.8097; r =0.6958); and a weaker correlation for diastema (r = 0.656, r = 0.3938) for male & female respectively. The left side of the hemiarch showed a higher success rate (82%) in comparison to right side (72%). Statistically significant differences were also found between the types of arches for both right and left side (p<0.005).Conclusion: The present study would be useful for stature estimation to the forensic experts.